In planta removal of nptII selectable marker gene from transgenic tobacco plants using CRISPR/Cas9 system. - Rezaei, A.; Farsi, M.; Malekzadeh-Shafaroudi, S.; Seifi, A.
Removal of selectable marker genes (SMGs)from genetically engineered (GE)plants is desirable because of the concerns about their probable negative effects on human health, other organisms and the environment. Different strategies are used to remove SMGs from GE plants including genome editing technologies. In this study, neomycin phosphotransferase II (nptII)selectable marker gene was successfully excised from the transgenic tobacco plants using CRISPR/Cas9 system. We relied on in planta transformation to surpass tissue culture procedure, which is costly and time-consuming. The plant leaves were agroinfiltrated by a Bean yellow dwarf virus (BeYDV)- based vector carrying Cas9 and sgRNAs designed based on the coding sequence of the nptII gene. After six days local and systemic leaves were collected and the presence of the viral vector and excision of nptII was checked using PCR. The presence of the virus in local and systemic leaves was detected. Also, excision of the nptII gene in local leaves was confirmed. Excision of the nptII sequence was significant in flower buds as a systemic tissue at flowering stage. Due to the systemic spread of the excising gene cassette, it is expected to have the nptII removed from the genome in the germlines, and thus, it is possible to have offspring free of the nptII gene. These findings present virus-base vectors as a promising method to edit plants genomes in planta.
Keywords: GENOME EDITING; CRISPR/CAS9; SELECTABLE MARKER GENE; IN PLANTA TRANSFORMATION; VIRAL VECTORS